Wheat allergy in children – new tools for diagnostics. Issue 11 (November 2014) - Mäkelä, M. J.; Eriksson, C.; Kotaniemi‐Syrjänen, A.; Palosuo, K.; Marsh, J.; Borres, M.; Kuitunen, M.; Pelkonen, A. S.
Summary Background The detection of wheat‐specific IgE in children often leads to a suspicion of wheat allergy, but little information is available on the most reliable wheat allergens for predicting clinical reactivity. Objective To evaluate the role of allergenic components of wheat in wheat allergy diagnostics. Methods One hundred and eight children (median age 1.5 years; range 0.6–17.3 years) with suspected wheat allergy underwent open or double‐blinded, placebo‐controlled oral wheat challenges. Responsiveness to different allergenic components of wheat was studied by skin prick tests and by determination of serum IgE antibodies using a semi‐quantitative microarray assay. Results Thirty (28%) children reacted with immediate symptoms, and 27 (25%) with delayed symptoms to ingested wheat, whereas 51 (47%) children exhibited no reactions in oral wheat challenges. Positive IgE responses to any of the 12 allergenic components of wheat was seen in 93%, 41%, and 43% of those with immediate, delayed or no reactions to ingested wheat, respectively (P < 0.001 to P < 0.05 in every comparisons between those with immediate reactions and those with no reactions). Positive IgE responses to ≥5 different allergenic components improved significantly the diagnostic accuracy (with a positive likelihood ratio (LR+) of 5.10). Alpha‐amylase inhibitors (AAI), in particular dimeric AAI 0.19 (LR+ 6.12), alpha‐, beta‐, and gamma‐gliadins (LR+ from 3.57 to 4.53), and high‐molecular‐weight (HMW) glutenin subunits (LR+ 4.37) were the single allergenic components of wheat differentiating most effectively those with immediate symptoms from those who did not exhibit any reactions. Conclusions and Clinical Relevance Wheat allergy diagnostics is difficult, even using sophisticated component methods. Our results confirm earlier findings about gliadins and identify the dimeric AAI 0.19, as a relevant allergen in clinically reactive patients when compared to non‐reactive subjects. The accuracy of wheat allergy diagnosis may be improved by measuring IgE responses to several components of wheat.